Biocatalytic Potential of Enzymes Involved in the Biosynthesis of Isoprenoid Quinones. Issue 1 (2nd October 2017) - Aleku, Godwin A.; Nowicka, Beatrycze; Turner, Nicholas J.
Abstract: Naturally occurring isoprenoid quinones mediate electron transfer in respiratory or photosynthetic chains of living organisms. Tremendous progress has been made in the elucidation of biosynthetic pathways of prenylated quinones and a number of enzymes that catalyze specific transformation steps with remarkably high regio‐ and stereoselectivity have been characterized. Interestingly, some of these enzymes possess broad substrate scope towards synthetic analogues, thereby enabling their application as synthetic tools. The availability of mechanistic, structural and mutagenesis information for many of the pathway enzymes presents opportunities for protein engineering, a powerful approach that may improve the suitability of these biocatalysts for industrial processes. Abstract : This Minireview discusses the biocatalytic applicability of key enzymes for the biosynthesis of isoprenoid quinones. Proof of concept of synthetic applications of these biocatalysts and efforts made to engineer them are highlighted.